Molecular basis of glucose-6-phosphate dehydrogenase deficiency in Cape Coast, Ghana - Bonsu, Dan Osei Mensah (2014)
A thesis submitted to the Department of Biochemistry and Biotechnology, Kwame Nkrumah University of Science and Technology. Kumasi, in partial fulfilment of the requirements for the degree of Master of Science